Socio-Cultural inequality in women’s health service utilization in Nepal - United Nations (Asia-Pacific Population Journal, 2017)
This paper investigates caste/ethnicity based inequity in women’s health service utilization, particularly focusing on antenatal care (ANC) in the socioculturally complex patriarchal context of Nepal. Numerous studies worldwide have examined the effects of various factors contributing to antenatal care. However, much less is known about the influence of caste/ ethnicity on women’s health-care utilization in Nepal. Using the nationally representative Nepal Demographic Health Survey (NDHS) Data 2011, a multilevel logistic regression was run with results suggesting that both non-economic (caste/ethnicity) and economic (household wealth) factors influence women’s health-care utilization. First, women who belong to a disadvantaged caste/ethnicity such as the Hill Janajati, Hill and Terai Dalit and Muslims are significantly less likely to make four plus antenatal care visits compared to the advantaged Bahun/Chhetri mothers. Second, mothers who belong to the wealthier category are significantly advantaged in terms of using antenatal care services compared to the poorest category of mothers. Third, contrary to the common assumption, mothers from the advantaged caste/ethnicity (Bahun/Chhetri and Newar) do not always fare better in all aspects of life; when from the poorest households, they are not significantly different in terms of antenatal care compared the poorest mothers who are from a disadvantaged caste/ethnicity. These findings offer evidence against the misassumption that individuals of advantaged caste/ ethnicities are always privileged, suggesting that health policies should take into account the intertwining effects of both caste/ethnicity and economic status in order to improve women’s health and well-being.